2018
DOI: 10.3788/col201816.020016
|View full text |Cite
|
Sign up to set email alerts
|

Dual-wavelength Bi2Se3-based passively Q-switching Nd3+-doped glass all-fiber laser

Abstract: We demonstrate a dual-wavelength passively Q-switched Nd 3þ-doped glass fiber laser using a few-layer topological insulator Bi 2 Se 3 as a saturable absorber (SA) for the first time, to the best of our knowledge. The laser resonator is a simple and compact linear cavity using two fiber end-facet mirrors. The SA is fabricated by Bi 2 Se 3 /polyvinyl alcohol composite film. By inserting the SA into the laser cavity, a stable Q-switching operation is achieved with the shortest pulse width and maximum pulse repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The largest pulse energy was 111.2 nJ, while the highest peak power was 76.3 mW. As mentioned, 6.6 mW output power and 38.8 nJ pulse energy have been obtained by Rong et al within a passively Nd-doped fiber laser [25], in their work, with Bi 2 Se 3 nanosheet prepared by the liquid-phase exfoliation method employed as the SA. Obviously, our experiment results exhibit higher average output power and larger pulse energy, indicating that CVD-Bi 2 Se 3 exhibits significant advantages in demonstrating pulse lasers with high output power and large pulse energy.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The largest pulse energy was 111.2 nJ, while the highest peak power was 76.3 mW. As mentioned, 6.6 mW output power and 38.8 nJ pulse energy have been obtained by Rong et al within a passively Nd-doped fiber laser [25], in their work, with Bi 2 Se 3 nanosheet prepared by the liquid-phase exfoliation method employed as the SA. Obviously, our experiment results exhibit higher average output power and larger pulse energy, indicating that CVD-Bi 2 Se 3 exhibits significant advantages in demonstrating pulse lasers with high output power and large pulse energy.…”
Section: Resultsmentioning
confidence: 85%
“…In addition, actively Q-switched Nd-doped fiber laser operations were also reported by different groups [21][22][23][24]. Recently, Rong et al have reported a dual-wavelength Bi 2 Se 3 -based passively Q-switching Nd-doped glass all-fiber laser [25]. The laser resonator comprised a simple and compact linear cavity using two fiber end-facet mirrors, which achieved a stable Q-switching operation with the shortest pulse width and maximum pulse repetition rate of 601 ns and 205.2 kHz, respectively.…”
Section: Introductionmentioning
confidence: 95%